Adoption of digital transformation from a firm’s creation to decline: the role of China’s mass entrepreneur and innovation campaign - Umer Sahil Maqsood; Qian Li; R. M. Ammar Zahid (Financial Innovation)
Abstract Following the global economy’s shift toward a digital-based system, the significance of digital transformation (DT) at the firm level has become increasingly important. Accordingly, this study aims to enhance understanding of a firm’s DT by examining the varying impacts ofirm life cycle (FLC) stages on DT adoption. We consider the impact of the mass entrepreneur and innovation campaign (MEIC) on this relationship. Based on the data of China A-share non-financial companies listed on the Shanghai and Shenzhen stock exchanges from 2010 to 2020. The baseline findings reveal that firms in the growth stage are likelier to adopt DT than firms in the introduction and decline stages; however, DT adoption in the maturity stage is uncertain. MEIC encourages DT adoption during the introduction, maturity, and decline stages. Furthermore, the univariate test demonstrates a relative enhancement in DT after implementing MEIC, underscoring its role in effectively allocating resources within the firms to embrace DT. This study’s results are robust across various estimation techniques and instrumental variables. The empirical results offer insights into policy implications, highlighting the factors shaping firms’ DT adoption decisions at different FLC stages and endorsing resource-based and agency theories.